The evolving Lebanese drug crisis: Trends in drug availability and affordability for common outpatient diseases from 2019 to 2023. - Rachel Jaber Chehayeb; Shashwat Kala; Huwayda Abou Ghannam; Ghassan Hasan; Joe Salloum (Public Library of Science (PLoS), 2023)
Since 2019, Lebanon has been suffering from an enduring economic crisis, that in conjunction with the COVID-19 Pandemic and the Beirut Port Explosion, has had catastrophic consequences on many facets of the Lebanese healthcare system. However, few studies have operationalized the impact of the crisis on drug availability and affordability. This is particularly relevant given that Lebanon imports approximately 95% of pharmaceutical products. Toward this end, we evaluated trends in outpatient drug availability and affordability in the context of monthly mean income at three time points throughout the evolving economic crisis (pre-crisis-August 2019, early crisis- August 2021, most recent-April 2023). Drugs used to treat the most common causes of mortality in Lebanon were selected from the Lebanese Ministry of Public Health (MOPH)'s List of Essential Medications. Drug pricing was obtained from the Lebanese MOPH National Drug Database. We found large increases in drug prices, as a percentage of mean monthly income, after subsidies on chronic disease medications were removed. Diabetes and COPD drugs were the least affordable in 2023, amounting to 21.03% and 15.43% of mean monthly income, respectively. We also highlight great shortages in drugs across classes, particularly in mood-stabilizing psychiatric drugs and basal and bolus insulin. Our findings highlight the growing financial burden of chronic disease treatment in Lebanon and the importance of implementing both short- and long-term solutions to mitigate the impact of the crisis on public health.